Cyclic tests of four two-story narrow steel plate shear walls. Part 2 experimental results and design implications. - Li, Chao-Hsien
This paper is the second part of a two-part paper presenting the cyclic tests of four two-story narrow steel plate shear walls (SPSWs). The first paper introduces the analytical studies and the specimen designs. This paper describes the test results. Some design implications including the capacity design for the first story column and the width-to-thickness ratio check for the beam web are discussed based on key observations from the tests. Test results confirm that the simplified strip model can accurately predict the inelastic responses of the specimens. Test results also confirm that the proposed capacity design method is effective in ensuring the plastic hinge formation at the bottom end of the first story column for SPSW with or without restrainers. Test results also show that the horizontal restrainers are effective in reducing the member forces in the boundary beam and column elements. Comparing the test results of the typical SPSW with those of the restrained SPSW (R-SPSW) specimens, it is found that the R-SPSW possesses an improved cyclic performance and reduced material weight. Analytical results predict the compressed column moments at the onset of the column plastic hinge formation well. The analytical hysteretic energy distribution in the first story column agrees very well with the observed inelastic actions developed in the four specimens. The detailed frame response analyses and the test results confirm that the assumptions made in developing the proposed column capacity design method are reasonable.
Keywords: Steel plate shear wall (SPSW).; Restrained steel plate shear wall (R-SPSW).; Capacity design; Narrow steel plate shear wall